Synthesis and characterization of new metal-free and metal-substituted phthalocyanine compounds and study Molecular docking - Hussein Ali Al-Bahrani (Academia One, 2024)
A newly of cobalt and nickel derivative of phthlocyanine were synthesized. Tetra nitro cobalt phthalocyanine, tetra-(5-amino-2-hydroxybenzoic) cobalt phthalocyanine were synthesized and recrystalized. By adding 5-aminosalicylic acid, tetra-(5-amino salicylic acid) Cobalt phthalocyanine was synthesized. Nickel derivatives were synthesized via the same pattern. Phthalocyanine without metal is synthesized also. All the derivatives were separated, recrystallized and identified using FTIR, 1H NMR, and UV spectroscopy. The molecular docking study was addressed in this work and reviled a promising biological activities especialy the compound with molecule not containing metal element.
Keywords: Nickel phthalocyanine; Cobalt phthalocyanine; metal-free phthalocyanine